CLIMATE CHANGE ACTION THROUGH VISUAL AND PERFORMING ARTS: A PERSPECTIVE FOR SOCIAL TRANSFORMATION - Vinay Kumar; MA, Suhel (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Climate change is an existential reality for mankind and requires immediate attention and community action. Globally, various approaches are being adopted to influence policy and community awareness and behaviour. Art serves as a bridge, connecting scientific facts with human experiential understanding of nature, making the intricacies understood in simple yet impactful ways, and reducing the existing gaps. The intersection of climate change action and use of the visual and performing arts represents an attractive area that synergizes artistic expression with environmental activism. This paper reviews and explores the various forms of these arts serving as powerful channels to involve, connect, and inspire zeal among communities on climate change action. These art forms have been part of every human culture since time immemorial and generate diverse perspectives and emotional responses with great potential for desired social change. Further, visual and performing arts have played a critical role in breaking down social and cultural barriers among masses to desired behavioural change by addressing pertinent socio-cultural politics. By sustainably using these art forms and chronicles, the social change agents by involving proficient artists can contribute to long-term community enrichment and societal transformation towards climate action. The rich potential of visual and performing arts to not only satiate human minds abstracts but also raise awareness and mobilize communities, influence policy, and ultimately drive meaningful climate activism and social transformation for a climate-smart and sustainable world.